صكوك الإجارة ودورها فى دعم الوقف الإسلامي : دراسة تحليلة فقهية لوقف الملك عبد العزيز آل سعود للحرمين الشريفين - وادو، حلمي حاجي (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2011)
The basis of this study "Sukuk Ijarah (Ijarah Bonds) and its Role in Support of the Islamic Waqaf: An Analytical Jurisprudence Study to the Endowment of King Abdul-Aziz for the Two Holy Mosques" is to highlight the importance of the reconstruction of endowments that do not generate revenue or neglect dilapidated endowments through Sukuk Ijarah, since it is represented as a financial and successful investment instrument, especially in infrastructure investment. The study mainly shows the effectiveness of Sukuk Ijarah in financing the construction of a huge real estate – the Zamzam Tower - without causing a deficit on the budget of the state. In theory, the study sheds light on the concepts of the Endowment and Ijārah bonds by addressing their legitimacy. It addresses generally the history of the endowment before and after Islam, and particularly its origin and development in the Kingdom of Saudi Arabia before the establishment of the state until the present day. The study also addresses the issue of securitization and its origin in the Western world and Islamic world by illustrating examples of Muslim countries that have applied and issued those instruments. It is noted that the approach used in this study is the descriptive inductive approach based on tracking and collecting views, opinions, and evidences of scholars on the issues of the endowment and Sukūk Ijārah as an instrument of investment. The analytical approach is also used in this study, as the researcher discusses and analyzes the views and opinions as well as evidences on the investment of endowments according to the system of Sukūk Ijārah. The sample of Zamzam Tower within the project of King Abdul Aziz Endowment for the Two Holy Mosques is used as a case study to identify the generated positives and negatives behind the implementation of Sukūk Ijārah. The sample will also be compared to other contracts such as acquisition (Hakr), time sharing, and tawarruq. In conclusion, the implementation of Sukūk Ijarah or the so-called bonds of benefit in Zamzam Tower is considered a legal and legitimate contract to indicate that the transfer of property ownership do take place by the beneficiary or the buyer (holder) of the bonds to benefit the leased premises for a certain period in a year within the twenty-four years without any guarantee of purchase by the sponsoring state of the project. The beneficiary has the right over the leased premise in the forms of personal utility, grant, sell or the re-leasing of bonds.